Discovery of Pleurotus cystidiosus (Agaricales, Pleurotaceae) in the north of Mexico - Lizarraga Escobar, Marcos (2024)
Abstract: Background and Aims: Some species of Pleurotus form anamorphs that produce coremia and arthrospores, which are classified in the subgenus Coremiopleurotus and are morphologically very similar. In Mexico, seven species of the genus are known; however, only P. smithii, described from Mexico City, is known to form coremia. Recent collections of Pleurotus from Chihuahua, Mexico, showed distinct characteristics from the known spe cies for the country, whose morphological and molecular characterization allowed us to identify P. cystidiosus in Mexico. The objective of this work was to document the presence of P. cystidiosus in Mexico and provide a detailed description of the specimens found in the country.